Studi Komparatif Tentang Kebebasan Wanita Dalam Perspektif Hak Asasi Manusia (HAM) Dan Ajaran Hadis - Nadila Nur Karimah; Aziz Miftahus Surur; Bustanul Arifin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study is motivated by the conceptual dilemma between women's freedom in the perspective of Human Rights (HR), which demands total non-discriminatory freedom, and the teachings of hadith, which apply boundaries based on moral values and Islamic law, especially in student environments. The main problem addressed is how to realize proportional freedom for women, enabling freedom of expression, dress, and social participation to be implemented without negating either human rights or religious norms. This research applies a comparative analysis method via literature review and expert interviews, focusing on the three aspects of freedom. The findings reveal that the HR perspective provides broad opportunities for women's freedom, yet its application requires boundaries to avoid conflicting with collective values in religious societies. In contrast, the hadith approach emphasizes a balance between individual rights and moral responsibility, guided by ethics, the principles of amar ma’ruf nahi munkar, and covering the aurat. The study concludes that synergistic integration of universal HR principles and Islamic values in the practice of women's freedom within educational settings is necessary to foster character that is free, responsible, moral, and harmonious.